Social Capital and Knowledge Creation: Diminishing Returns of the Number and Strength of Exchange Relationships - McFadyen, M. Ann; Cannella, Albert A. (Academy of Management Journal, 2004)
This study analyzed the relationship between social capital and knowledge creation at the individual level. Our limited theory of knowledge creation encompasses the number and strength of the relationships that a person maintains. Hypothesis tests in a sample of biomedical research scientists strongly supported predictions. As relationships increased in number, returns to knowledge creation diminished. Increased interactions with a single other showed a similar effect. The strength of interpersonal relations had a higher marginal effect on knowledge creation than the number of relations.